Answer:
![f = (1)/(2\pi )\sqrt{(g)/(L)}](https://img.qammunity.org/2020/formulas/physics/college/fosurt7i8k9m4z32ijvjst9m59eatt6r7u.png)
Step-by-step explanation:
Let the mass of bob in the simple pendulum is m and the effective length of the pendulum is L.
The value of acceleration due to gravity is g.
Let the pendulum is tilted by a small angle θ from the vertical.
The component of force which restore its position is given by
F = - m g Sinθ
(negative sign shows the opposite direction of displacement and the force)
If angle θ is small, then Sinθ = θ
F = - m g θ
According to diagram, θ = s / L
So, F = - m g s / L
Acceleration, a = F / m
a = - g x / L
As a ∝ - s
So, it is Simple harmonic motion.
Compare by A = - ω² s
Here,
ω² = g / L
We know that, ω = 2 Π f, where f is the frequency of oscillations.
So,
4 π²f² = g / L
![f = (1)/(2\pi )\sqrt{(g)/(L)}](https://img.qammunity.org/2020/formulas/physics/college/fosurt7i8k9m4z32ijvjst9m59eatt6r7u.png)